2011
DOI: 10.1136/thoraxjnl-2011-201054c.39
|View full text |Cite
|
Sign up to set email alerts
|

P39 Nutritional assessments in COPD: the respiratory nurse perspective on current practice across the UK

Abstract: (ISW), Chronic Respiratory Disease Questionnaire (CRDQ), MRC Dyspnoea score (MRC) and COPD assessment test (CAT) were measured. Between group differences were compared using ManneWhitney U or unpaired t-test. Results Data are presented as median (25 th , 75 th centiles), and summarised in Abstract P37 table 1. 130 COPD patients from this cohort were taking either an ACE-I (n¼82), ARB (n¼45) or both (n¼3). The groups were matched for gender distribution and longterm oral corticosteroid use. Compared with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Future longitudinal studies and randomised controlled trials are required to further define the effect of ACE-I and ARB in COPD.Introduction and ObjectivesTargeting nutritional status is a key issue in COPD. Studies have shown increased mortality in patients with low BMI 1 which improves following weight gain 2. This study examines whether nutritional status is adequately assessed and acted upon in COPD patients admitted to a DGH.…”
mentioning
confidence: 99%
“…Future longitudinal studies and randomised controlled trials are required to further define the effect of ACE-I and ARB in COPD.Introduction and ObjectivesTargeting nutritional status is a key issue in COPD. Studies have shown increased mortality in patients with low BMI 1 which improves following weight gain 2. This study examines whether nutritional status is adequately assessed and acted upon in COPD patients admitted to a DGH.…”
mentioning
confidence: 99%